(untitled) (Journal of NELTA, 2018)
Integrating culture into language contexts in EFL classroom has been an issue of substantial concern for years. Different methods or approaches have been introduced for the integration of culture and language learning. Recently, project-based learning (PBL) seems to be a favorite choice among methodologists. This paper analyzes the syllabi of a drama project and a cultural project to address cultural aspects in PBL in EFL classrooms. The findings show that PBL provides opportunities to enhance and improve students’ language skills and soft skills. More importantly, a wide range of knowledge of different cultural perspectives may be collected during the projects. Journal of NELTA, Vol 20 No. 1-2, December 2015, page 5-15